THE EFFECT OF TRAINING AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT MATAHARI PUTRA PRIMA TBK (HYPERMART) CIMANGGIS BRANCH, DEPOK, WEST JAVA - Farida, Syarifah Ida; Tajuddien, Rahadyan; Romansyah, Yowan (International Journal of Social and Management Studies, 2023)
The purpose of this study was to analyze the effect of training and motivation on employee performance. The type of research used is quantitative research methods, the research location is at PT Matahari Putra Prima Tbk (Hypermart) Cimanggis Depok Branch. The sample collection method uses a saturated sample of 69 employees, collecting data using a Likert scale questionnaire. The collected data were analyzed using multiple linear regression. The results of the study show that training and motivation partially and simultaneously have a significant effect on employee performance